Biophysical phenotypes and determinants of anterior vs. posterior primitive streak cells derived from human pluripotent stem cells. (1st March 2019) - Lin, Feng; Shao, Yue; Xue, Xufeng; Zheng, Yi; Li, Zida; Xiong, Chunyang; Fu, Jianping
Graphical abstract: Abstract: Formation of the primitive streak (PS) marks one of the most important developmental milestones in embryonic development. However, our understanding of cellular mechanism(s) underlying cell fate diversification along the anterior-posterior axis of the PS remains incomplete. Furthermore, differences in biophysical phenotypes between anterior and posterior PS cells, which could affect their functions and regulate their fate decisions, remain uncharacterized. Herein, anterior and posterior PS cells were derived using human pluripotent stem cell (hPSC)-based in vitro culture systems. We observed that anterior and posterior PS cells displayed significantly different biophysical phenotypes, including cell morphology, migration, and traction force generation, which was further regulated by different levels of Activin A- and BMP4-mediated developmental signaling. Our data further suggested that intracellular cytoskeletal contraction could mediate anterior and posterior PS differentiation and phenotypic bifurcation through its effect on Activin A- and BMP4-mediated intracellular signaling events. Together, our data provide new information about biophysical phenotypes of anterior and posterior PS cells and reveal an important role of intracellular cytoskeletal contractility in regulating anterior and posterior PS differentiation of hPSCs. Statement of Significance: Formation of the primitive streak (PS) marks one of the most important developmental milestones in embryonic development. However, molecular and cellular mechanism(s) underlying functional diversification of embryonic cells along the anterior-posterior axis of the PS remains incompletely understood. This work describes the first study to characterize the biophysical properties of anterior and posterior PS cells derived from human pluripotent stem cells (hPSCs). Importantly, our data showing the important role of cytoskeleton contraction in controlling anterior vs . posterior PS cell phenotypic switch (through its effect on intracellular Smad signaling activities downstream of Activin A and BMP4) should shed new light on biomechanical regulations of the development and anterior-posterior patterning of the PS. Our work will contribute significantly to uncovering new biophysical principles and cellular mechanisms driving cell lineage diversification and patterning during the PS formation.